A Case Study and a Computational Simulation of the European Union Draft Technical Guidance Documents for Chemical Safety Assessment of Mixtures: Limitations and a Tentative Alternative - Kim, Jongwoon; Kim, Sanghun; Schaumann, Gabriele E. (TAYLOR & FRANCIS INC, 2013)
Two different methods, Key Critical Component (KCC) and Composite Reciprocal (CR), are used to derive Predicted No Effect Concentration (PNECs) and Derived No Effect Level (DNELs) that are employed in mixture risk assessment. A case study was conducted on coating products and a computational simulation of the KCC and CR methods. The KCC method considers only one key critical component as the whole mixture of equal danger, whereas the CR method indirectly considers the contribution of each component to mixture toxicity. Computational simulation is the first approach that adopts a theoretical perspective in discussing the causes of different outcomes between models and how the two methods should be applied for regulatory purposes in terms of concept, implementation, and performance. The deviation between the two models was highly dependent on the number of mixture components having similarly weighted DNELs (or PNECs). Therefore, if risk assessment using the KCC or CR method needs to be achieved, then the number of mixture components with similarly weighted DNELs (or PNECs) should be checked first. In this study, as a tentative alternative to the existing KCC and CR methods, a tiered approach combining Enhanced KCC (e-KCC) and CR methods was proposed and discussed. [Supplementary materials are available for this article. Go to the publisher's online edition of Journal of Occupational and Environmental Hygiene for the following free supplemental resources: Material Safety Data Sheets for coating products.]